Trabecular complexity as an early marker of cardiac involvement in Fabry disease. (22nd January 2021) - Camporeale, Antonia; Moroni, Francesco; Lazzeroni, Davide; Garibaldi, Silvia; Pieroni, Maurizio; Pieruzzi, Federico; Lusardi, Paola; Spada, Marco; Mignani, Renzo; Burlina, Alessandro; Carubbi, Francesca; Econimo, Laura; et al.
Abstract: Aims: Fabry cardiomyopathy is characterized by glycosphingolipid storage and increased myocardial trabeculation has also been demonstrated. This study aimed to explore by cardiac magnetic resonance whether myocardial trabecular complexity, quantified by endocardial border fractal analysis, tracks phenotype evolution in Fabry cardiomyopathy. Methods and results: Study population included 20 healthy controls (12 males, age 32±9) and 45 Fabry patients divided into three groups: 15 left ventricular hypertrophy (LVH)-negative patients with normal T1 (5 males, age 28±13; Group 1); 15 LVH-negative patients with low T1 (9 males, age 33±9.6; Group 2); 15 LVH-positive patients (11 males, age 53.5±9.6; Group 3). Trabecular fractal dimensions (Dfs) (total, basal, mid-ventricular, and apical) were evaluated on cine images. Total Df was higher in all Fabry groups compared to controls, gradually increasing from controls to Group 3 (1.27±0.02 controls vs. 1.29±0.02 Group 1 vs. 1.30±0.02 Group 2 vs. 1.34±0.02 Group 3; P <0.001). Group 3 showed significantly higher values of all Dfs compared to the other Groups. Both basal and total Dfs were significantly higher in Group 1 compared with controls (basal: 1.30±0.03 vs. 1.26±0.04, P =0.010; total: 1.29±0.02 vs. 1.27±0.02, P =0.044). Total Df showed significant correlations with: (i) T1 value ( r =−0.569; P <0.001); (ii) LV mass ( r =0.664, P <0.001); (iii) trabecular mass ( r =0.676; P <0.001); (iv) Mainz Severity Score Index ( r =0.638; P <0.001). Conclusion: Fabry cardiomyopathy is characterized by a progressive increase in Df of endocardial trabeculae together with shortening of T1 values. Myocardial trabeculation is increased before the presence of detectable sphingolipid storage, thus representing an early sign of cardiac involvement.